PERAN DOMPET DHUAFA DALAM PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM DOMPET DHUAFA FARM BANTEN - Atik Dinan Nasikha (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2021)
The presence of DD Farm Banten helps the community around Gowok Kepuh Village, Sukajaya District, Serang City in economic empowerment, especially in the agricultural sector. DD Farm has a few activity, one of their activity is fattening & breeding. Based on the background, the formulation of the problem in this study are: 1). How are the society condition in Gowok Kepuh Village, Sukajaya Village, Curug District, Serang City? 2). What’s about the role of Dompet Dhuafa in community empowerment carried out at DD Farm Banten? 3). What are the support and the obstacle factor on carry out the program? This study aims to explain: 1) to find out the condition of the community in Gowok Kepuh Village, Sukajaya Village, Curug District, Serang City. 2). To find out the role of Dompet Dhuafa in community empowerment carried out at DD Farm Banten. 3). To find out the factors that support and obstacle when they’re carry out the program. Based on the research that has been done, the writer find out that: the educational condition of the society in Gowok Kepuh village is still low. Economic conditions are still below the minimum wage in Serang city. Open social conditions, and easy to accept new people. The role of Dompet Dhuafa by creating DD Farm Banten in which it is focused on the farm program, namely Fattening & breeding. The supporting factors of the program are: qualified human resources (HR)/staff, and available facilities. The inhibiting factors are: beneficiaries who easily leave DD Farm Banten, weather, location of DD Farm Banten, and Investors.